2010
DOI: 10.1007/s10571-010-9542-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Glutamate Scavenging on Cortical Evoked Potentials

Abstract: It is well known that traumatic or ischemic brain injury is followed by acute excitotoxicity caused by the presence of abnormally high glutamate (Glu) in brain fluids. It has recently been demonstrated that excess Glu can be eliminated from brain into blood following the intravenous administration of oxaloacetate (OxAc), which, by scavenging blood Glu, induces an enhanced and neuroprotective brain-to-blood Glu efflux. In this study, we subjected rats to intravenous OxAc administration (i.v., 12.5, 25, and 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Previous studies done by our group and others have shown that pharmacologically reducing blood glutamate levels with glutamate scavengers (such as oxaloacetate and pyruvate) limit glutamate neurotoxicity and provide better neurologic outcomes after various brain insults, particularly traumatic brain injury [14,[19][20][21][44][45][46][47][48][49][50][51][52][53]. Unfortunately, although these treatments have been shown to be effective in animal models of stroke, traumatic brain injury, and subarachnoid hemorrhage, their use in humans is limited by Food and Drug administration restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies done by our group and others have shown that pharmacologically reducing blood glutamate levels with glutamate scavengers (such as oxaloacetate and pyruvate) limit glutamate neurotoxicity and provide better neurologic outcomes after various brain insults, particularly traumatic brain injury [14,[19][20][21][44][45][46][47][48][49][50][51][52][53]. Unfortunately, although these treatments have been shown to be effective in animal models of stroke, traumatic brain injury, and subarachnoid hemorrhage, their use in humans is limited by Food and Drug administration restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is an efflux mechanism for glutamate as blood-mediated scavenging is reported to reduce glutamate in the cerebrospinal fluid (Gottlieb et al 2003). There is some evidence that this may offer some protection (Zlotnik et al 2008; Teichberg et al 2009; Zlotnik et al 2010; Nagy et al 2010). The mechanism, however, of release from the brain remains to be identified.…”
Section: Glutamate Transporters At the Blood Brain Barriermentioning
confidence: 99%
“…60 Blood glutamate scavenging can be enhanced further by adding recombinant GOT to oxaloacetate. 61,62 The ability of blood glutamate scavenging to decrease brain glutamate levels was demonstrated in vivo in a model of brain ischemia in the rat using magnetic resonance spectroscopy. 63 The neuroprotective effect of blood glutamate scavenging has been confirmed in a number of experimental conditions associated with high brain concentrations of glutamate, such as traumatic brain injury, epilepsy, and ischemic stroke.…”
Section: Is Blood Glutamate Scavenging a Viable Strategy To Alleviatementioning
confidence: 99%